Tanggung Jawab Rumah Sakit Swasta Dalam Pelayanan Kesehatan Bagi Peserta BPJS Kesehatan di Kota Mataram - Mualifah, Mualifah (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2020)
Health services are provided through the form of medication and care. Health workers, medical and non-medical, are responsible for providing optimal service. Medical personnel, in this case doctors, have responsibility for the treatment that is being carried out. Treatment actions and determining needs in the treatment process are the authority of the doctor. In accordance with the formulation of the problem and the research objectives, this legal research uses a normative or dogmatic approach to law as its main approach, with the aim of examining its positive law in the sense of collecting, presenting, systematizing, analyzing, interpreting and assessing positive legal norms that protect people's rights. BPJS health participants. Health effort is any activity to maintain and improve health, which aims to create an optimal health plan for the community. The community has the same rights in gaining access to resources in the health sector, for this reason government hospitals and private hospitals are responsible for providing health services to the community. Private hospitals in collaboration with BPJS Kesehatan are required to provide health services to BPJS Kesehatan participant patients without discriminating against BPJS Kesehatan participants who are referred by first level health facilities, namely puskesmas and family doctors according to their interests